Metode Terapi Hipnopunktur (Hipnoterapi Dan Terapi Akupunktur) Untuk Peningkatan Kualitas Hidup Pasien Kanker Rahim Pasca Kemoterapi Di Kota Surakarta - Maria Dewi Christiyawati; Sri Yatmihatun; Sumanto Sumanto (Jurnal Keterapian Fisik, 2016)
Abstract: Uterine Cancer Is A Gynecologic Malignancy Is Most Common In Women, One Of Its Kind Is A Uterine Sarcoma. Uterine sarcoma is a rare tumor that dominates 3% of uterine cancer. Myoma uteri can cause malignancy although his case is rare. In Indonesia, the proportion of myoma uteri reach 2.39 to 11.7% of all gynecological patients. Chemotherapy is a treatment for uterine cancer drugs of the use of drugs to kill or slow the growth of cancer cells that can cause side effects. The side effects that can be felt by people with cancer of the uterus such as feeling sick, vomiting, feeling tired, weight loss, hair loss, loss of appetite and difficulty sleeping. Approximately 70-100% of chemotherapy patients experience fatigue / fatigue. Fatigue felt by patients with this cancer will also affect the quality of life penderita.Terapi acupuncture in cancer patients can be done to overcome the side effects of chemotherapy either by research or classical theory. The research method was quasi experimental design with pre -post test design without control group. Data were taken before and after administration of therapeutic intervention hipnopunctur. Data dianlisis using t-test, independent t-test multiple linear regression. Number of samples 14 people. Results obtained significance value (p) = 0.000 compared with the value ᾳ = 0:05 (5%), where the value of P <0.05, which means that a significant difference between the methods Hipnopunkture with improved quality of life. Values obtained -0824 t test. The value of the coefficient is between 0.8 -1.0 interval which indicates the degree of influence between these variables is very strong.